Professional social science education teacher in increasing competence - Siswoko; Muhammad Ruhiyat; Yayan Sudrajat (Journal of Instructional Development, Innovation, and Evaluation, 2022)
The purpose of writing this article is to improve teacher competence in accordance with the Law on Teachers and Lecturers Number 14 of 2005 article 10 that teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in age education. early education, basic education, and secondary education through formal education. Teacher competencies include pedagogic, personality, social, and professional competencies obtained through professional education. Keywords: pedagogic competencies, personality competencies, social competencies, and professional competencies